O validnosti eksperimental'nych issledovanij - Orechov, L.; Karavaeva, E. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The problem of the methodology of science, in particular, validity, i.e. validity of conclusions by the results of experimental researches is discussed in the article. the sequence of the analysis of the factors influencing the internal and external validity of the experiments is shown on concrete examples.